Co-Citation Analysis and Burst Detection on Financial Bubbles with Scientometrics Approach - Zhou, Wei; Chen, Jin; Huang, Yang (Economic research - Ekonomska istraživanja, 2019)
It is found that financial crises generally happen accompanied by the collapse of financial bubbles. Therefore, many scholars have carried out researches on financial bubbles. In this paper, we analyse the current status and explore the development of financial bubbles with scientometric technique. By downloading and analysing 1048 articles from Web of Science, the main findings of this paper are: 1) Three hot topics in the financial bubble research are 'Ledoit-Sornette financial bubble model', 'European Union emission trading scheme' and 'agent-based model'; 2) the current research status of financial bubble is clearly demonstrated by the most productive subject categories, countries, institutions, journals, authors, and cited articles; 3) the investigations that related to 'Chinese stock market' contribute significantly in the financial bubble research; and 4) the burst detection analysis shows that the new trends in recent years are 'asset price bubble', 'herd behaviour', 'crashes', and 'econophysics'. Therefore, this paper provides the knowledge domain, the overall intellectual structure, and the emerging trends of the financial bubble research by analysing the status quo, the co-citations, and the burst detection, which presents more accurate and comprehensive insights into research topics and research development trends over time from various perspectives.